DEPENDENCE OF CARIES INTENSITY IN INDIVIDUALS OF THE KHARKIV REGION AND THE AJACENT AREAS POPULATION, BORN WITH MACROSOMIA, ON THE BODY MASS INDEX AT BIRTH - Garmash, O.V. (World of Medicine and Biology, 2019)
The total of 220 persons aged 11 – 55 years has been examined. The indices of caries are determined, the hygienic state of oral cavities is assessed, the mixed saliva secretion rate and the rate of minor salivary glands secretion are assessed, the number of salivary glands per a definite area is calculated for all participants, and the status of acid-alkaline balance of the oral fluid is estimated in 140 persons, who were born with fetal macrosomia, and in 80 persons, who were born with fetal normosomia (whose parameters at birth were normal). These groups have a proportional representation of age and sex. The conclusion has been made that among the participants of the study, who were born macrosomes, in the period of permanent occlusion, the highest values of caries indices (caries intensity index and significant caries index) are characteristic of macrosomic-at-birth persons born with intrauterine obesity. Individuals born with macrosomia have, on average, a reliably reduced number of minor salivary glands per an area unit, a reduced rate of the mixed saliva secretion and a reduced rate of the minor salivary glands secretion as compared to those whose parameters at birth were normal.